Learners’ Perceived Roles and Competencies of Tutors in a Distance Education Program of a Public University in Malaysia - Chang, Yee Yar (2008)
Reaching the world through distance education is the current trend of education. However, distance education is different than the traditional mode of education as it involves physical separation between the learner and the teacher. Thus, facilitating learning in a distance required the use of different knowledge, skills and attitudes. Distance education tutor is one of the main elements to the success of distance education; therefore, it is important for tutors to equip themselves with appropriate skills and knowledge. This study aims to explore the roles and competencies of distance education tutors from students’ perspective. A comprehensive list of distance education tutor’s roles,and competencies focus on Berge four areas of study, namely pedagogical role, social role, managerial role and technical role was provided to students in order to rate the importance of each role and competency, to study perception of students with different background (course, demographic and general information) for the roles and competencies of tutors and to find out whether there is any gap exists between tutors’ required and acquired competencies. The identification of specific roles and competencies within a discipline serves as a useful guide in creating effective professional development. The study used quantitative research methodology. Among the employed statistic were non-parametric statistic with means calculation; standard deviation; frequency distribution; T-Test; ANOVA and Pearson Product-Moment Correlation. A total of 128 distance education students studying in eight learning centers provided by Center for External Education or Pusat Pendidikan Luar (PPL), Universiti Putra Malaysia (UPM) in Sabah and Sarawak had participated in this study. The average means score for each role and competency were calculated and ranked according to their importance. The result showed that “Social Role” (total means = 28.16) was the most important role for a distance education tutor to perform, while “Managerial Competencies” (total means = 31.42) was the most important competencies they should possess. The findings indicated that it is important for distance education tutors to take into consideration the different needs and priorities shown by different groups of students, such as their gender, their field of study, the distance between their house and the learning center, their level of experience with Internet tools and their level of interaction with their tutors outside the tutorial session, with the roles and competencies of their distance education tutors. It has also been found that gaps existed between the required and acquired competencies among distance education tutors, with the biggest gap in “Pedagogical Competencies” and the smallest in “Social Competencies”.